Antibiotische Therapie vs. Appendektomie bei nichtperforierter Appendizitis im Erwachsenenalter - Schölch, Sebastian; Reißfelder, Christoph (Der Chirurg, 2019)
For decades, the mandatory treatment for acute uncomplicated appendicitis was urgent appendicectomy. This dogma has now been questioned by several randomized controlled trials, which demonstrated the safety of antibiotic treatment of uncomplicated appendicitis without increased morbidity and mortality. The efficacy of this conservative treatment, however, is inferior to surgery: Within the first year after antibiotic treatment of acute appendicitis, approximately 30% of patients require appendicectomy. Within 5 years the rate of appendicectomy increases to 40% and the life-long risk of appendicectomy after conservative treatment can be expected to be even higher. The advantages of conservative treatment of appendicitis are faster recovery and the lack of postoperative wound pain; however, all currently available trials compared conservative treatment almost exclusively with conventional appendicectomy, trials comparing laparoscopic appendicectomy to antibiotics are currently not available. As laparoscopic appendicectomy is a well-established and safe treatment ubiquitously available in Germany, conservative treatment in patients with uncomplicated appendicitis cannot generally be recommended. As antibiotic treatment is a less effective but equally safe procedure, it can be offered to selected patients only.